2020
DOI: 10.1016/j.canlet.2020.02.037
|View full text |Cite
|
Sign up to set email alerts
|

HPV + HNSCC-derived exosomal miR-9 induces macrophage M1 polarization and increases tumor radiosensitivity

Abstract: Human papillomavirus (HPV) is an etiological risk factor for a subset of head and neck squamous cell carcinoma (HNSCC). HPV+ HNSCC is significant more radiosensitive than HPV-HNSCC, but the underlying mechanism is still unknown. Tumor microenvironment can affect tumor response to radiation therapy. Cancer secreted exosomes are emerging as crosstalk mediators between tumor cells and the tumor microenvironment. The main objectives of this study were to determine the role of HPV+ HNSCC-derived exosomes in increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…Further evidence showed that thrombospondin 1 (THBS1) derived from OSCC EXOs is involved in the polarization of macrophages towards an M1-like phenotype and creates conditions that promote OSCC progression [114]. MiRNA-9-rich EXOs derived from HPV (+) HNSCC lead to polarization of macrophage M1 via downregulation of peroxisome proliferator-activated receptor δ (PPARδ) and increase the radiosensitivity of tumours [115]. Hence, miRNA-9 may be used as a potential treatment for HNSCC.…”
Section: The Effects Of Tumour-derived Evs On Immune Cellsmentioning
confidence: 99%
“…Further evidence showed that thrombospondin 1 (THBS1) derived from OSCC EXOs is involved in the polarization of macrophages towards an M1-like phenotype and creates conditions that promote OSCC progression [114]. MiRNA-9-rich EXOs derived from HPV (+) HNSCC lead to polarization of macrophage M1 via downregulation of peroxisome proliferator-activated receptor δ (PPARδ) and increase the radiosensitivity of tumours [115]. Hence, miRNA-9 may be used as a potential treatment for HNSCC.…”
Section: The Effects Of Tumour-derived Evs On Immune Cellsmentioning
confidence: 99%
“…Protein targeting plays key role in cancer signaling such as evading growth repressors, angiogenesis, and metastasis signaling therefore contribution of miR-9-5p contribution can’t be ignored. Also, there is a recent study which found miR-9 enriched in HPV infected HNSCC patients and downregulates PPARD to induce macrophage polarization[47]. miR-1 is enriched in ARP2/3 complex mediated actin nucleation and regulation of actin filament polymerization also in transport and localization.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of CD47, a supposed antiphagocytic molecule, on HPV(+) TEX might support prolonged interactions with immune cells [49]. Recently, HPV(+) TEX were found to foster M1 polarization of macrophages via miR-9, which may contribute to radiosensitivity of HNSCC [50].…”
Section: Molecular and Functional Profiles Of Exosomes From Hpv(+) Anmentioning
confidence: 99%